Relative Age Effects and contextual factors in male Spanish youth football: a 10-year cross sectional analysis of U12 to U16 players - Peña-González, Iván; Fernández-Jávega, Gonzalo; Castellano-Galvañ, Ismael; Moya-Ramón, Manuel (Frontiers in Sports and Active Living, 2025)
IntroductionThe Relative Age Effects (RAEs) are complex, multifactorial phenomena influenced by individual (e.g., maturity status), task-related (e.g., field position or competitive level), and environmental (e.g., coaches' expectations) factors. This cross-sectional study aimed to investigate the relationship between RAEs and the maturity status, field position, competitive level and coaches' expectations within a sample of 1,120 young male Spanish football players [mean age: 13.72 ± 1.40 years; weight: 54.09 ± 11.85 kg; height: 162.11 ± 11.38 cm; years from peak height velocity (PHV): −0.22 ± 1.44], across tree age categories (U12, U14 and U16).MethodsData was collected over 10 years (2014–2024), considering the maturity status, estimated using the Mirwald et al. (2002) formula. Physical performance was assessed through tests for strength (1RM), power, speed (30-m sprint), agility (T-test), jumping (CMJ), and aerobic endurance (estimated VO2max). Players' field positions and coaches' efficacy expectations about their players were also collected.ResultsA Chi-square (χ²) analysis revealed a skewed distribution across birth quartiles within age categories (p < 0.05). Pearsons' correlation and linear regression analyses showed significant relationship between relative age and maturity status (r = 0.91; R² = 0.84). The RAEs were more pronounced at higher competitive levels, while the distribution bias in playing positions was comparable to the overall sample, with the exception of goalkeepers in the U12-14 categories. ANOVA results tend to a higher physical performance and coaches' efficacy expectations for players with higher RA in the U14 and U16 categories.ConclusionThis study confirms the presence of strong RAEs over the past decade in youth football players from U12 to U16. Individual and environmental factors, such as advanced maturity status, the intensified selection processes at higher competitive levels, an increased physical performance and higher coaches' efficacy expectations, may contribute to RAEs in a complex and interdependent manner.